Price Discrimination and Monopolistic Competition - Katz, Michael L. (Econometrica, 1984)
[I examine the effects of price discrimination on the equilibrium prices, number of firms, and level of total surplus in a monopolistically competitive market. The main finding is that uniform pricing is more (less) efficient than is price discrimination when the purchases made by the consumers who are discriminated against constitute a small (large) proportion of the total purchases.]